2018
DOI: 10.1186/s12879-018-3325-0
|View full text |Cite
|
Sign up to set email alerts
|

Incident HIV infection has fallen rapidly in men who have sex with men in Melbourne, Australia (2013–2017) but not in the newly-arrived Asian-born

Abstract: BackgroundWe examined differences in incident HIV infection between newly-arrived Asian-born and other men who have sex with men (MSM) after the introduction of universal HIV treatment guidelines in 2015 and pre-exposure prophylaxis in 2016.MethodsClinical, demographic, laboratory and behavioural data on MSM presenting for HIV testing at the Melbourne Sexual Health Centre from July 2013 to June 2017 were extracted. We compared the proportion of newly-arrived (four years or less in Australia), Asian-born and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 20 publications
2
48
0
Order By: Relevance
“…A review by Tanser and colleagues (2015) also identified poorer HIV diagnosis and care cascades among migrants and found that existing health system structures failed to properly account for migrants who still present late and have poor retention [29]. In Australia, the incidence of HIV in newly arrived Asian-born MSM was found to be higher than other subpopulations [30]. Although Medicare ineligibility is a significant barrier, it is known that migrants are less likely to be offered or less likely to initiate early ART despite having access [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…A review by Tanser and colleagues (2015) also identified poorer HIV diagnosis and care cascades among migrants and found that existing health system structures failed to properly account for migrants who still present late and have poor retention [29]. In Australia, the incidence of HIV in newly arrived Asian-born MSM was found to be higher than other subpopulations [30]. Although Medicare ineligibility is a significant barrier, it is known that migrants are less likely to be offered or less likely to initiate early ART despite having access [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Reports suggest recently arrived Asian MSM are an emergent risk group for HIV in Australia 3,4 . In Victoria, of 299 new HIV diagnoses reported in 2017, 125 were of overseas‐born individuals, 60% of whom were born in Asia 5 .…”
mentioning
confidence: 99%
“…Enhanced testing for early diagnosis, effective antiretroviral treatment and the recent Pharmaceutical Benefits Scheme listing of pre‐exposure prophylaxis have reduced new HIV infections in high risk populations. This reduction is greatest in men who have sex with men (MSM), a broad term which includes gay‐identified men, heterosexually identified MSM and bisexual men . Significant improvements in early initiation of antiretroviral treatment provide individual as well as public health benefits .…”
Section: Hiv and Sexually Transmitted Infectionsmentioning
confidence: 99%
“…However, new diagnoses in the Aboriginal and Torres Strait Islander population increased by 41% compared with a decline of 12% in the non‐Indigenous population between 2013 and 2016 . Despite the overall reduction among MSM in major cities, subpopulations such as bisexual men (who may be less likely to access HIV prevention and testing services than gay‐identified MSM) and Asian‐born MSM continue to be at high risk . The decrease in consistent condom use among gay and bisexual men since the introduction of pre‐exposure prophylaxis has led to an increase in the burden of bacterial STIs, particularly rectal chlamydia infections, and warrants attention .…”
Section: Hiv and Sexually Transmitted Infectionsmentioning
confidence: 99%